El mecanismo en La máquina de Joseph Walser : una aproximación al fundamento literario de El Reino de Gonçalo M. Tavares (2020)
The following thesis seeks to establish a possible hierarchy of values that explains many of the actions and behaviors of the marginal characters that star in the tetralogy of El Reino. Due to the above, the relevance of the mechanism will be assimilated, within the novels, as the culmination of a series of relationships that have a certain value within the microcosm created by Gonçalo M. Tavares. Although important parallels are established between the four novels grouped in El Reino, this text places special emphasis on Un hombre: Klaus Klump and La máquina de Joseph Walser. According to the previous reasoning, the reader will find a detailed analysis based mainly on four argumentative axes. The first of them concerned with the thematic and spatial continuity between the author's creations; the second for the function of animals and nature in relation to the other characters...